STUDI KINERJA SIMPANG BERSINYAL PERGERAKAN LALU LINTAS KOTA PAREPARE - Novianti, Elva; T, M. Natshir; Andriyani (Jurnal Karajata Engineering, 2023)
Jl. General Ahmad Yani and Jl. A. Mappangara are at a signalized intersection in Parepare City. Because the traffic flow is quite dense, especially during rush hours, this intersection has the potential to cause accidents, congestion, and delays. This study aims to determine the existing condition of the intersection and the performance of the signalized intersection on Jl. General Ahmad Yani–Jl. A. Mappangara Kota Parepare. The method used is quantitative, namely data management in the form of numbers with data analysis using the MKJI 1997 method, which was carried out in March 2021. The results of the research show that the results of data analysis on traffic flow patterns are busiest on Mondays, with afternoon peak hours at 17.00–18.00 WITA. The value of the number of vehicles on the north arm is 1149 pcu/hour, the east arm is 319 pcu/hour, and the south arm is 705 pcu/hour. Performance that occurs at the intersection with a degree of saturation of 0.92 and an average delay of 53.00 sec/smp. The level of road service on the 3 approaches shows poor service with a LOS (Level Of Service) value on the North arm of 43.2 is E, the East arm is 84.51 is F, and the South arm is E. Where the flow is unstable, the traffic volume is quite heavy.